2008
DOI: 10.1007/s00011-007-7128-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of triptolide on interleukin-18 and its receptor in rheumatoid arthritis synovial fibroblasts

Abstract: TP effectively inhibited the expression of IL-18 and its receptor in PMA-stimulated RASF. These results suggest a mechanism of TP in RA therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Triptolide with 100 ng/ml concentration could inhibit inflammatory cytokine production of FLS and inhibit invasive capacities of FLS. Lu et al (2008) demonstrated that triptolide inhibits the expression of IL-18 and its receptor in PMA-stimulated FLSs in a dose-dependent manner by suppressing NF-κB activity. However, Lu et al (2008) only analyzed one inflammatory cytokine produced by FLS.…”
Section: Potential Effects Of Triptolide On Inflammatory Diseasesmentioning
confidence: 97%
See 1 more Smart Citation
“…Triptolide with 100 ng/ml concentration could inhibit inflammatory cytokine production of FLS and inhibit invasive capacities of FLS. Lu et al (2008) demonstrated that triptolide inhibits the expression of IL-18 and its receptor in PMA-stimulated FLSs in a dose-dependent manner by suppressing NF-κB activity. However, Lu et al (2008) only analyzed one inflammatory cytokine produced by FLS.…”
Section: Potential Effects Of Triptolide On Inflammatory Diseasesmentioning
confidence: 97%
“…Lu et al (2008) demonstrated that triptolide inhibits the expression of IL-18 and its receptor in PMA-stimulated FLSs in a dose-dependent manner by suppressing NF-κB activity. However, Lu et al (2008) only analyzed one inflammatory cytokine produced by FLS. Lin et al (2001) demonstrated that 28–140 nM triptolide suppresses the production of proMMP1 and 3 in IL-1α-induced FLSs.…”
Section: Potential Effects Of Triptolide On Inflammatory Diseasesmentioning
confidence: 97%
“…Conversely, the expression of tissue inhibitors of metalloproteinases (TIMPs) 1 and 2 induced by IL-1α was augmented by TP in the synovial cells [ 44 ]. In phorbol 12-myristate 13-acetate (PMA)-stimulated RA, the expression of IL-18 and IL-18 receptor (IL-18R) at protein and gene levels FLSs were also reduced by TP [ 45 ].…”
Section: Effect and Mechanisms Of Triptolide (Tp) In Rheumatoid Armentioning
confidence: 99%
“…In recent years, triptolide has been shown to exert excellent anti-inflammatory effects as an RA treatment (Peng et al, 2014; Fan et al, 2016). Among these studies, RA-FLS were identified as one of the main targets of triptolide for RA therapy (Lin et al, 2001, 2008; Kusunoki et al, 2004; Shao et al, 2004; Yao et al, 2005).…”
Section: Introductionmentioning
confidence: 99%